Adsorption mechanism and collapse propensities of the full-length, monomeric A beta(1-42) on the surface of a single-walled carbon nanotube: a molecular dynamics simulation study - Jana, Asis K.; Sengupta, Neelanjana (Biophysical Journal, 2012)
Though nanomaterials such as carbon nanotubes have gained recent attention in biology and medicine, there are few studies at the single-molecule level that explore their interactions with disease-causing proteins. Using atomistic molecular-dynamics simulations, we have investigated the interactions of the monomeric A beta(1-42) peptide with a single-walled carbon nanotube of small diameter. Starting with peptide-nanotube complexes that delineate the interactions of different segments of the peptide, we find rapid convergence in the peptide's adsorption behavior on the nanotube surface, manifested in its arrested movement, the convergence of peptide-nanotube contact areas and approach distances, and in increased peptide wrapping around the nanotube. In systems where the N-terminal domain is initially distal from nanotube, the adsorption phenomena are initiated by interactions arising from the central hydrophobic core, and precipitated by those arising from the N-terminal residues. Our simulations and free energy calculations together demonstrate that the presence of the nanotube increases the energetic favorability of the open state. We note that the observation of peptide localization could be leveraged for site-specific drug delivery, while the decreased propensity of collapse appears promising for altering kinetics of the peptide's self-assembly.

Adsorption of the full length amyloid beta peptide on the carbon nanotube surface and the thermodynamic implications for fibrillogenesis - Sengupta, Neelanjana; Jana, Asis K. (Biophysical Journal, 2012)
56th Annual Meeting of the Biophysical-Society, San Diego, CA, FEB 25-29, 2012

Critical roles of key domains in complete adsorption of a beta peptide on single-walled carbon nanotubes: insights with point mutations and MD simulations - Jana, Asis K.; Jose, Jaya C.; Sengupta, Neelanjana (Physical Chemistry Chemical Physics, 2013)
Owing to the influence of nanomaterials on biomacromolecular behavior, their potential applications are rapidly gaining attention. Based on atomistic molecular dynamics simulation studies we have recently reported that the full-length A beta peptide, whose self-assembly is associated with Alzheimer's disease, adsorbs rapidly on single-walled carbon nanotubes, thereby losing its natural propensity to collapse. Here, we investigate the mechanistic overlap between the peptide's compactification and its adsorption, while decoupling the roles of hydrophobicity and aromaticity via point mutations. The collapse mechanism is correlated with interactions between the central hydrophobic core (HP1) and the peptide's C-terminal domain, which are almost exactly compensated by interactions arising from the nanotube after complete adsorption. Adsorption is initiated by HP1 and consolidated by strong interactions arising from the N-terminal domain. Altering the hydrophobicity, but not the aromatic character, of the central residue in HP1 decreases the collapse probability. On the other hand, the adsorption propensity is dramatically reduced when either the hydrophobicity or the aromatic character in HP1 is compromised. The hydrophobicity of HP1 is responsible for dewetting transitions that facilitate its initial interactions with the nanotube, which then lead to very favorable interactions with the nanotube.

Surface induced collapse of A beta(1-42) with the F19A replacement following adsorption on a single walled carbon nanotube - Jana, Asis K.; Sengupta, Neelanjana (Biophysical Chemistry, 2013)
Spontaneous adsorption of the A beta peptide on the surface of a single-walled carbon nanotube, resulting in the prevention of its intrinsic propensity to form collapsed states, could be a plausible means to hinder the peptide's initial nucleation and self-assembly. We report here the effects of sharply reducing both aromatic and hydrophobic character within the peptide's central hydrophobic core on its free and surface behavior. In such an altered peptide, complete surface adsorption is found to induce, rather than prevent, the adsorbed peptide's collapse. The weakened surface interactions of the central hydrophobic core allow its greater translational mobility on the surface, thereby facilitating interactions that lead to compaction. Both the adsorption and the subsequent collapse are accompanied by a loss of surface hydration in the modified peptide. We further find that such a two-step dewetting leads to hydration levels comparable to that obtained after compaction of the free peptide. These insights may be leveraged for designing molecular surfaces for disrupting intrinsic A beta behavior. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Amyloid beta peptide; carbon nanotube; Lateral mobility; molecular dynamics simulation; Surface induced collapse

Atomistic simulations lend mechanistic insights into plausible ways of perturbing the nucleation thermodynamics of the full-length a beta peptide - Jana, Asis K.; Sengupta, Neelanjana (Biophysical Journal, 2014)
58th Annual Meeting of the Biophysical-Society, San Francisco, CA, FEB 15-19, 2014

Molecular investigations of protriptyline as a multi-target directed ligand in alzheimer's disease - Bansode, Sneha B.; Jana, Asis K.; Batkulwar, Kedar B.; Warkad, Shrikant D.; Joshi, Rakesh S.; Sengupta, Neelanjana; Kulkarni, Mahesh J. (Plos One, 2014)
Alzheimer's disease (AD) is a complex neurodegenerative disorder involving multiple cellular and molecular processes. The discovery of drug molecules capable of targeting multiple factors involved in AD pathogenesis would greatly facilitate in improving therapeutic strategies. The repositioning of existing non-toxic drugs could dramatically reduce the time and costs involved in developmental and clinical trial stages. In this study, preliminary screening of 140 FDA approved nervous system drugs by docking suggested the viability of the tricyclic group of antidepressants against three major AD targets, viz. Acetylcholinesterase (AChE), beta-secretase (BACE-1), and amyloid beta (A beta) aggregation, with one member, protriptyline, showing highest inhibitory activity. Detailed biophysical assays, together with isothermal calorimetry, fluorescence quenching experiments, kinetic studies and atomic force microscopy established the strong inhibitory activity of protriptyline against all three major targets. The molecular basis of inhibition was supported with comprehensive molecular dynamics simulations. Further, the drug inhibited glycation induced amyloid aggregation, another important causal factor in AD progression. This study has led to the discovery of protriptyline as a potent multi target directed ligand and established its viability as a promising candidate for AD treatment.

Beta self-association and adsorption on a hydrophobic nanosurface: competitive effects and the detection of small oligomers via electrical response - Jana, Asis K.; Sengupta, Neelanjana (Soft Matter, 2015)
Treatment of Alzheimer's disease (AD) is impeded by the lack of effective early diagnostic methods. Small, soluble A beta globulomers play a major role in AD neurotoxicity, and detecting their presence in aqueous fluids could lead to suitable sensors. We evaluate the adsorption behavior of small A beta oligomers on the surface of a single walled carbon nanotube of high curvature. While the intrinsic self-assembly propensity of A beta is markedly hindered by adsorption, the oligomeric units show high degrees of surface immobilization. Immobilized complexes are capable of oligomeric growth, but with a shifted monomer-oligomer equilibrium compared to the free states. In the presence of an ionic solution and suitable external electric fields, magnitudes of the current blockades are found to be sensitive to the oligomeric number of the adsorbed complex. However, this sensitivity gradually diminishes with increasing oligomeric size. The results provide a proof-of-concept basis for further investigations in the design of sensors for detecting the toxic small oligomers of A beta.

Tolbutamide induces conformational change and promotes albumin glycation - Bansode, Sneha B.; Batkulwar, Kedar B.; Warkad, Shrikant D.; Jana, Asis K.; Sengupta, Neelanjana; Kulkarni, Mahesh J. (RSC Advances, 2015)
Tolbutamide is a first generation sulfonylurea drug used for the treatment of type II diabetes. In the present study, the effect of tolbutamide on albumin conformation was investigated using BSA as a model protein. The binding of tolbutamide induced a conformational change in albumin, which was confirmed by thioflavin T assay, ANS assay, and CD spectroscopy. Computer simulations suggested that the binding of tolbutamide increases the solvent accessibility of lysine residues, the hotspots of glycation. Furthermore, the change in conformation of albumin facilitates increased glycation, which was observed by AGE specific fluorescence and the results were corroborated by mass spectrometric analysis. This study suggested that tolbutamide enhances albumin glycation by inducing conformational change in BSA and hence could be a potential risk factor if used for a prolonged period.

Glycation induces conformational changes in Amyloid-? peptide and enhances its aggregation propensity: molecular insights - Jana, Asis K.; Batkulwar, Kedar B.; Kulkarni, Mahesh J.; Sengupta, Neelanjana (Physical Chemistry Chemical Physics, 2016)

Hydralazine inhibits amyloid beta (Aβ) aggregation and glycation and ameliorates Aβ1–42 induced neurotoxicity - Batkulwar, Kedar B.; Jana, Asis K.; Godbole, Rashmi K.; Khandelwal, Puneet; Sengupta, Neelanjana; Kulkarni, Mahesh J. (RSC Advances, 2016)

Unraveling origins of the heterogeneous curvature dependence of polypeptide interactions with carbon nanostructures - Jana, Asis K.; Tiwari, Mrityunjay K.; Vanka, Kumar; Sengupta, Neelanjana (Physical Chemistry Chemical Physics, 2016)
Emerging nanotechnology has rapidly broadened interfacial prospects of biological molecules with carbon nanomaterials (CNs). A prerequisite for effectively harnessing such hybrid materials is a multifaceted understanding of their complex interfacial interactions as functions of the physico-chemical characteristics and the surface topography of the individual components. In this article, we address the origins of the curvature dependence of polypeptide adsorption on CN surfaces (CNSs), a phenomenon bearing an acute influence upon the behavior and activity of CN-protein conjugates. Our benchmark molecular dynamics (MD) simulations with the amphiphilic full-length amyloid beta (A beta) peptide demonstrate that protein adsorption is strongest on the concave (inner) CN-surface, weakest on the convex (outer) surface, and intermediary on the planar surface, in agreement with recent experimental reports. The curvature effects, however, are found to manifest non-uniformly between the amino acid subtypes. To understand the underlying interplay of the chemical nature of the amino acids and surface topography of the CNs, we performed high-level quantum chemical (QM) calculations with amino acid analogs (MA) representing their five prominent classes, and convex, concave and planar CN fragments. Molecular electrostatic potential maps reveal pronounced curvature dependence in the mixing of electron densities, and a resulting variance in the stabilization of the non-covalentty bound molecular complexes. Interestingly, our study revealed that the interaction trends of the high-level QM calculations were captured well by the empirical force field. The findings in this study have important bearing upon the design of carbon based bio-nanomaterials, and additionally, provide valuable insights into the accuracy of various computational techniques for probing non-bonded interfacial interactions.

Structural and dynamics studies of the TetR family protein, CprB from Streptomyces coelicolor in complex with its biological operator sequence - Bhukya, Hussain; Jana, Asis K.; Sengupta, Neelanjana; Anand, Ruchi (Journal of Structural Biology, 2017)
In Streptomycetes, tetracycline repressor family of transcription regulators (TetR-FTRs) controls various biological processes including antibiotic biosynthesis, cellular morphology and innate resistance. Here, we focus on understanding the structural basis of transcription regulation by CprB, a member of TetR-FTRs from S. coelicolor. CprB is implicated as a receptor of gamma-butyrolactones, a class of quorum sensing molecules, responsible for initiating secondary metabolic pathways. In order to understand the molecular mechanism of DNA recognition, the X-ray structure of CprB in complex with its biological relevant operator sequence was solved to a resolution of 3.95 angstrom. Furthermore, to refine and compliment the results, atomistic molecular dynamics simulations were carried out using the X-ray structure as the template. The studies reveal that CprB binds to DNA as dimer of dimers with this mode of interaction results in minimal distortion in the DNA, enabling these proteins to recognize multiple sequences with varying affinity. Another crucial finding from our simulation results was that the positively charged N-terminal arm of CprB brings extra stability to the protein-DNA complex by interacting with the minor-groove of the DNA and anchoring itself to the phosphate backbone. Corroborating electrophoretic mobility shift assay and fluorescence anisotropy experiments showed that the mutant AN6-CprB exhibited about 7-8 fold reduced DNA binding. Comparison with other TetR-FTRs reveals that this strategy is also employed by over 25% of TetR-FTRs, where N-terminal anchoring mechanism is used to enhance selectivity for a particular DNA sequence. (C) 2017 Elsevier Inc. All rights reserved.